The impact of shocks on gender-differentiated asset dynamics in Bangladesh - Rakib, Muntaha; Matz, Julia Anna (International Food Policy Research Institute, 2014)
Assets are an important means of coping with adverse events in developing countries but the role of gendered ownership is not yet fully understood. This paper investigates changes in assets owned by the household head, his spouse, or jointly by both of them in response to shocks in rural agricultural households in Bangladesh with the help of detailed household survey panel data. Land is owned mostly by men, who are wealthier than their spouses with respect to almost all types of assets, but relative ownership varies by type of asset.